SOCIO-ECONOMIC DEVELOPMENT OF UZBEKISTAN IN THE POST-PANDEMIC PERIOD - Karimov Diyor Mukhtarovich; Sultanova Lola Sharapovna (Journals Park Publishing, 2022)
Quarantine restrictions have made significant adjustments to the implementation of the plans for the socio-economic development of Uzbekistan, from which the economies of almost all countries of the world have suffered. In the context of the exit from the pandemic, the economy of Uzbekistan began to gradually return to its previous level. In this regard, it is important to continue the implementation of reforms aimed at increasing the competitiveness of the economy.
Keywords: Uzbekistan, economy, pandemic, consequences, reforms.